PENGARUH KUALITAS INFORMASI DAN PEMENUHAN KEBUTUHAN INFORMASI PADA YOUTUBE CHANNEL “GADGETIN” TERHADAP KEPUTUSAN PEMBELIAN GADGET - Nurul Aini; Sendi Eka Nanda (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study aims to determine how much influence the quality of information and the fulfillment of information needs on Youtube channel gadget GadgetIn on purchasing decisions. This type of research uses descriptive quantitative method. Mechanical withdrawal sampling using purposive sampling technique. Uses and gratification theory is used as the theoretical foundation of this research. Methods of data collection using the questionnaire in the spread on 400 respondents who fit the criteria that researchers Youtube channel GadgetIn subscribers aged 20-25 years. Based on the research quality of information (X1) on purchasing decisions gadget (Y) has the effect of 18.1%, the results of research on meeting the needs of information on Youtube channel GadgetIn (X2) on purchasing decisions gadget (Y) has the effect of 26%, simultaneously the quality of information and the fulfillment of the Youtube channel GadgetIn information on purchasing decisions gadget has an influence 28.5%. The result of determination coefficient of 28.5%, which means fulfillment on Youtube channel information GadgetIn affected the quality of information, while the remaining 71.5% influenced by other factors.